NUMERICAL ANALYSIS OF THE NATURAL CONVECTION IN HORIZONTAL ANNULI AT LOW AND MODERATE Ra - Padilla, E. L. M.; Campregher, R.; Silveira-Neto, A. (Revista de Engenharia Térmica, 2006)
The natural convection at low and moderate Rayleigh numbers (Ra) in cylindrical horizontal annuli with imposed temperatures in both surfaces is numerically studied. This flow inside concentric cylinders classic configuration has a wide range of practical and technological applications, which justifies its growing studies efforts. In this work, the governing equations are discretized by the volume finite technique over a staggered grid, with second-order accuracy in space and time. The flow pattern is presented by several Rayleigh numbers, with an analysis of the heat transfer coefficient and flow properties. Furthermore, a three-dimensional field is shown at a moderate Ra number. The results showed a good agreement with the experimental data.